Potensi Kertas Koran dan Gabus sebagai Alternatif Material Akustik - Hedy C. Indrani, Priscilla Gloria (Intra, 2014)
Newspaper will be made and thrown daily so that the newspaper waste will not be finished that a lot of people can utilize the newspaper waste as body accessories or interior. A lot of paper research is done to decrease the number of logging. Paper has good chemical and natural ingredients so that the paper waste can be recycled into various form. Due to the huge number of newspaper and the texture that it has, it brings the idea to the writer to create a acoustic wall panel that not only function as the aesthetic but also technically that create a comfortable room in acoustic. Beside newspaper, a lot of waste will be used to support the function of acoustic panel itself. The research this time use a room of Sekolah Wisma Musik Symphony that located on the roadside, which need an economic and efficient acoustic treatment. The research method that is used is quantitative method through user interview, field survey, trial error test until the right composition of the panel is found that can be used to eliminate the problem in the Sekolah Wisma Musik Symphony room itself. The experiment that is done resulting in the composition of newspaper : (kasting) is 1 : 3 (duck spoon). While the composition of the panel itself is the processed newspaper : cork : (multipleks) is 3 : 3 : 0.6 (cm) that can absorb 96% of sound.